Repository Universitar - Duca Robert Ionuț (My University, 2025)
This diploma project aims to investigate the available platforms for digital archiving, including open-source solutions, and the implementation of such a solution at Transilvania University of Brașov. The initiative is aligned both with national plans for the development of digital infrastructure for open science - in particular through the participation of the university in the National Open Science Cloud Initiative (EN-NOSCI) - and with European guidelines for promoting transparency in research in South-East Europe, reflected in the NI4OS-Europe project. At the national level, there is a lack of a coherent policy for the promotion and adoption of open access practices to research results, which contributes to their marginal presence in the public space. Facilitating open access to scientific information could have a significant impact on the academic community and civil society, stimulating inter-institutional cooperation and strengthening the dissemination of knowledge to citizens.